Amino group of salicylic acid exhibits enhanced inhibitory potential against insulin amyloid fibrillation with protective aptitude toward amyloid induced cytotoxicity. Issue 5 (19th January 2018) - Zaman, Masihuz; Khan, Mohsin Vahid; Zakariya, Syed Mohammad; Nusrat, Saima; Meeran, Syed Mustapha; Alam, Parvez; Ajmal, Mohammad Rehan; Wahiduzzaman, Wahiduzzaman; Shahein, Yasser E.; Abouelella, Amira M.; Khan, Rizwan Hasan
Abstract: Protein misfolding and aggregation lead to amyloid generation that in turn may induce cell membrane disruption and leads to cell apoptosis. In an effort to prevent or treat amyloidogenesis, large number of studies has been paying attention on breakthrough of amyloid inhibitors. In the present work, we aim to access the effect of two drugs, that is, acetylsalicylic acid and 5‐amino salicylic acid on insulin amyloids by using various biophysical, imaging, cell viability assay, and computational approaches. We established that both drugs reduce the turbidity, light scattering and fluorescence intensity of amyloid indicator dye thioflavin T. Premixing of drugs with insulin inhibited the nucleation phase and inhibitory potential was boosted by increasing the concentration of the drug. Moreover, addition of drugs at the studied concentrations attenuated the insulin fibril induced cytotoxicity in breast cancer cell line MDA‐MB‐231. Our results highlight the amino group of salicylic acid exhibited enhanced inhibitory effects on insulin fibrillation in comparison to acetyl group. It may be due to presence of amino group that helps it to prolong the nucleation phase with strong binding as well as disruption of aromatic and hydrophobic stacking that plays a key role in amyloid progression. Abstract : The present study demonstrates that acetylsalicylic acid (ASA) and 5‐aminosalicylic acid (5‐ASA) inhibit fibrillation of insulin and amino group of salicylic acid was found to be more effective in inhibition over acetyl group. This may be due to presence of amino group on aromatic ring of 5‐ASA, which makes it more efficient in prolonging the nucleation stage of insulin aggregation through comparatively strong binding with amyloid prone region of proteins.